The Cuban Experience in Latin America (historical study) (Journal of the College of Basic Education, 2023)
Cuba is one of the most important countries on the Latin American continent (1), and the source of this importance is its distinguished geographical location. Cuba consists of a relatively large rectangular island, and a group of approximately 4,195 small islands in the open Caribbean Sea. And along the Tropic of Cancer at the Gulf of Mexico, 140 km from the island of Jamaica in its southwest, and 180 km from the US state of Florida in its northeast (2).One of the references indicates that the name Cuba is derived from the name of the Indian tribes (Cubana Skan) that were inhabiting the island during the European geographical exploration of it (3), while another reference believes that the name Cuba means the main place that indicates Cuba’s distinguished location between Florida and America Central. Cuba is one of the largest Caribbean islands, with an area of approximately 110,922 square kilometers, with a population of (11) million Spanish-speaking people, according to the 1983 census, with a fifth (1/5) of this number residing in the capital, Havana, which is one of fourteen provinces. It consists of an administrative cup (4).